Design and Development of a Web-Based Boarding House Information System - Iqbal Aditya Ferryanto; Ruswanti, Diyah; Susilo, Dahlan (Yayasan Literasi Sains Indonesia, 2025)
Web-based information systems serve an essential function in promoting efficient and efficient information management in the digital era. The objective of this research is to create a web-based information system for boarding houses with 6 boarding house research objects. to address challenges often encountered in manual data management, such as data inaccuracies and difficulties in accessing information. The development process employs the Waterfall methodology, which includes phases including communication, planning, planning, execution, and upkeep. The coding language applied for in creating websites is JavaScript and uses a MySQL database. Where This system offers features tailored to the needs of boarding house seeker, house owners, and administrators. Testing using the System Usability Scale (SUS) involving 38 respondents resulted in a rating of 78.16, categorized as good usability (Grade B). These results indicate that the system provides a satisfactory user experience and supports increased efficiency in managing boarding house operations.